Investigating Rickettsia africae infection in Amblyomma hebraeum ticks in Mnisi, Bushbuckridge Municipality, South Africa - Morar-Leather, Darshana (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.